Effect of Vermicompost Tea on Faba Bean Growth and Yield. Issue 4 (2nd October 2018) - Chaichi, Wissem; Djazouli, Zahreddine; Zebib, Bachar; Merah, Othmane
Abstract: This study investigated the effect of vermicompost tea (VCT) as a natural foliar fertilizer in faba bean. To determine the effect of VCT at different doses on the growth and reproduction of faba bean, VCT was produced and three different concentrations (0, 10, and 20% VCT) were applied as a foliar fertilizer to faba bean plants. Plant height, number of flowers, and pods per plant as well as soluble sugars were measured weekly after treatment for a period of 11 weeks. Treated plants were larger and had more flowers per clump, as well as more clumps and pods per plant than the control. Moreover, treated plants reached the flowering stage at least 3 weeks earlier than the control. This could be explained by the presence of nutrients, humic acid, and probably hormones in VCT, which may positively affect growth, reproduction, and yield. Treatment at 10% VCT presented better values than 20% VCT. The latter contained more humic acid, which probably limited growth and flowering. The soluble sugar and protein contents were higher in treated plants, and the highest values coincided with the flowering and reproductive stages. Similarly, seeds produced by treated plants were richer in protein that control seeds. These results indicate that 10% VCT is a useful fertilizer to improve growth in faba bean. This study highlights the possibility of using VCT as a foliar fertilizer to increase growth in faba bean.